FINANCIAL INSTRUMENTS OF SUPPORT OF SMALL BUSINESS INFRASTRUCTURE SUBJECTS IN THE REGION - Danyleichuk, R. B. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The purpose of the article is to identify and provide theoretical substantiation of the necessary and appropriate steps to ensure the proper organization of support for small business infrastructure subjects in the region with the involvement of a wide range of modern financial instruments. The article states that the development of small business infrastructure subjects in the region depends to a large extent on the effectiveness of the financial process organization. In the context of the economic crisis and post-crisis development, key areas of regional financial policy to support the financial sustainability of small business infrastructure entities should be the accumulation of financial resources for their further targeting the expansion of the network of small business infrastructure subjects in depressed (backward) territories; optimization of sources of accumulation of financial resources through increased participation in grant and donor programs, maximum attraction of private investments; orientation towards the gradual introduction of new forms and methods for managing financial activities at the regional level, including through the application of program-targeted financing in the budget process; orientation to the accomplished tasks in order to maintain the high efficiency of the regional financial policy. As a result of the analysis, it was found that regional funds for entrepreneurship support are the most common tool for providing financial assistance to small businesses at the local level. In a context of significant reduction of lending to commercial banks, regional business support funds in most regions continued the implementation of credit programs for small and medium enterprises. An important direction for increasing the lending of small business infrastructure entities is the creation of a system of guarantees for bank loans. It was established that in order to fulfill the tasks related to the financial support of the activities of small business infrastructure subjects, it is necessary to take effective measures aimed at supporting the infrastructure of the financial market itself (financial intermediation entities), as well as expanding the range of relevant services that may be offered to the subjects of small business infrastructure. It is determined that one of the tasks of regional financial policy is to support an attractive investment climate, which would help to attract appropriate investment resources for the organization and implementation of productive entrepreneurial activity. It is proposed to create special (free) economic zones at the regional level in an area as an effective tool for optimizing financial policy in the region. One of the tasks of creating such zones may be to stimulate the development of small business infrastructure subjects. The necessity of further theoretical substantiation and formation of recommendations concerning the ways, conditions and resources necessary to support small business infrastructure subjects in the region with the use of modern financial instruments is indicated.